The Influence of Knowledge Management in Peruvian Disaster Risk - Calderón Aguirre, Carlos David (2020)
This article is based as the Theory of Knowledge Management can influence Disaster Risk Management in Peru; recognizes the importance of your application with the aim of contributing to increase the efficiency in the processes of Estimation of the Risk, Prevention and Response to the Disasters. Knowledge Management is a useful tool for managing, acquiring, analyzing, storing and sharing knowledge to solve the problems of Disaster Risk Management in Peru; at the same time, it provides the National Disaster Risk Management System with a common platform for inter-agency coordination and collaboration, the employment and use of knowledge as a further purpose to contribute to contribute to the protection of the human person and society.